Social learning theory and academic writing in graduate studies (Journal of Applied Learning and Teaching, 2022)
Over the past 20 years, the Organization for Economic Co-operation and Development has reported a median of 50% for dropout rates in doctoral programs, all disciplines combined (OECD, 2019). Among reasons for not graduating, PhD students identify a lack of experience and competencies with academic writing, impeding on their progression as students, but also as novice scholars (Litalien & Guay, 2015). Indeed, graduate students are required to undergo professional socialization, by engaging with other scholars, to learn the norms and practices of their respective research fields (Skakni, 2011). This paper aims at communicating preliminary results from a doctoral research to provide a greater understanding of peer learning in academic writing groups organized by Master’s and PhD students. The social learning theory developed by Bandura (1971) is used as a foundation to our study, with its self-efficacy concept at the forefront of our theoretical framework. In that regard, PhD students can develop confidence in their abilities to successfully complete writing projects based on four sources of influence: mastery experiences; vicarious experiences; social persuasion; and physiological and emotional states (Bandura, 2019). While studying a learning community composed of 4,000 graduate students, as an instrumental case study (Stake, 1995), we conducted semi-structured interviews with 25 PhD students, followed by a content analysis of transcripts using a qualitative data analysis software (NVivo12). Participants representing 12 Canadian universities and 14 scholarly disciplines shared significant learning experiences related to all four self-efficacy sources of influence. Of particular interest, findings revealed that PhD students gathering in public places (cafes, libraries, coworking spaces, museums, parks) increased their self-efficacy through peer learning (exchanging, observing, modelling). These results are presented with a view of recommending valuable strategies to develop academic writing competencies through social actions led by graduate students, in conjunction with institutional support in the context of higher education.